2014
DOI: 10.7557/3.3017
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of growth layer groups in dentine tissue of captive common dolphins <i>Delphinus delphis</i>

Abstract: Knowledge of age structure and longevity (maximum age) are essential for modelling marine mammal population dynamics. Estimation of age in common dolphins (Delphinus spp.) is primarily based on counting Growth Layer Groups (GLGs) in the dentine of thin, decalcified and stained sections of teeth. An annual incremental deposition rate was validated for Delphinus spp. 30-years ago through the use of tetracycline. However, it is not known if the pulp cavity becomes occluded in older individuals or GLGs continue to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 18 publications
1
19
0
Order By: Relevance
“…The two oldest dolphins, both long‐term captive dolphins, were ≥33 and ≥35 yr in age (see Murphy et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…The two oldest dolphins, both long‐term captive dolphins, were ≥33 and ≥35 yr in age (see Murphy et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Age was estimated based on counting growth layer groups in dentine tissue (see Murphy et al . for an overview of the methodology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lockyer et al (2010) reported that GLGs in the cementum of harbour seal tooth sections are more prominent with Toluidine Blue while haematoxylins such as Mayer's or Ehrlich's were better for dentine. Murphy et al (2014) suggested that Toluidine Blue may have a better affinity for tissues decalcified using organic acids and chelating agents. Lockyer (1993Lockyer ( , 1995 preferred Ehrlich's acid haematoxylin as it is more durable and does not fade so rapidly over time.…”
Section: Nammco Scientific Publications Volume 10 20mentioning
confidence: 99%
“…In more recent years, the development of commercially prepared mixtures of acids, such as RDO (Apex Engineering Products Corporation, Illinois, USA), has significantly lowered decalcification times to hours. Murphy et al (2014) investigated the use of 4 different decalcifying agents, and found that Formical-4™ (Decal Chemical Corporation, New York, USA) provided the best sections for age estimates of two captive short-beaked common dolphins known to be over 30 years old. However, decalcification took 4-6 weeks.…”
Section: Nammco Scientific Publications Volume 10 11mentioning
confidence: 99%